2018
DOI: 10.1177/0022022118782641
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid and Alternating Identity Styles as Strategies for Managing Multicultural Identities

Abstract: The article introduces the concept of cultural identity styles, strategies that individuals use for decision making about identity-relevant issues, and proposes that blending and alternating are two strategies that acculturating individuals activate to manage multiple cultural identities. Drawing on diverse samples from New Zealand, Mauritius, and Israel, we present two studies. The first describes the construction of the Multicultural Identity Styles Scale (MISS) and the validation of its Hybrid Identity Styl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
186
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(234 citation statements)
references
References 94 publications
(186 reference statements)
39
186
8
1
Order By: Relevance
“…First, how do the hybridizing-alternating and BII models relate to one another cross-sectionally? This question is important in terms of replicating prior cross-sectional work (e.g., Ward et al, 2018). The remaining questions are longitudinal and extend prior work.…”
Section: The Present Study: Research Questions and Hypotheseesmentioning
confidence: 80%
See 3 more Smart Citations
“…First, how do the hybridizing-alternating and BII models relate to one another cross-sectionally? This question is important in terms of replicating prior cross-sectional work (e.g., Ward et al, 2018). The remaining questions are longitudinal and extend prior work.…”
Section: The Present Study: Research Questions and Hypotheseesmentioning
confidence: 80%
“…On one hand, multiple cultural identities can operate in parallel without implying integration or conflict (Hong et al, 2000;Sirin & Fine, 2008) -suggesting that alternation can occur independently of BII blendedness and harmony (such as feeling Mexican at home and American at work). On the other hand, Roccas and Brewer (2002) suggest that alternating identities imply compartmentalization and conflict, and Ward et al (2018) found a significant negative relationship between alternating identities and BII harmony. In the present study, we aimed to provide more evidence regarding the links between the BII dimensions and bicultural alternating.…”
Section: Biculturalism and Bicultural Identitymentioning
confidence: 95%
See 2 more Smart Citations
“…From the perspective of acculturative strategies, second‐generation Arabs in Israel were found to more frequently use the hybrid and integrative identity style in relation to psychological well‐being. In contrast, their parents, the first generation, more often used the alternating identity style to resolve cultural conflict; this style was associated with poorer psychological adaptation (Ward, Tseung‐Wong, Szabo, Qumseya, & Bhowon, ).…”
Section: Value Mismatch—the Other Side Of the Storymentioning
confidence: 99%